Nutraceuticals and their role in promoting musculoskeletal healthy aging - Alalwan, T. A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Aging is a complex and gradual biological process that represents the major risk factor with respect to the development of chronic degenerative diseases, often associated with disability. Diet and nutrition, coupled with proper physical activity have a significant impact on the health status of the elderly with a decreased risk of disease being indicative of successful aging. Musculoskeletal conditions such as osteoporosis and sarcopenia are the most frequently reported disorders among the elderly community. Methods. This study presents a systematic review of the literature on the potential benefits of several nutraceuticals in promoting healthy aging and in reducing the risk of chronic diseases in elderly individuals. Results. Dietary components including vitamins (vitamin C, B vitamin and vitamin K) flavonoids (e.g., quercetin, anthocyanins, and isoflavones), minerals (e.g., magnesium, zinc and potassium) and other nutrients such phytoestrogens, amino acids, and omega-3 fatty acids help in slowing the aging process, which ultimately results in increased lifespan and longevity. Conclusions. This paper highlights the key nutrients and phytochemicals of nutraceutical importance for the healthy aging of the elderly population. Although the scientific literature provides evidences of therapeutic effectiveness of nutraceuticals, more in-depth clinical investigations are needed.